Temporal Analysis of Rainfall and Temperature of Ranchi, Jharkhand for Period 1975-2050 - Pandit, C. K.; Lal, A. K.; Singh, U. S. (Journal of Scientific Research, 2024)
The rainfall and temperature pattern of the study area Ranchi is analyzed for the period 1975-2023, and it is observed that the rainfall has an increasing trend for Annual, Monsoon, June, July, August, September, and October while temperature has an increasing trend for August only. The correlation between rainfall and average temperature emphasizes a negative correlation for annual, summer, March, May, and June at a 99 % confidence level while for July, September, and December, the correlation is negative at a 95 % confidence level. ARIMA(0,1,1) is chosen to be the most accurate model for the forecasting of rainfall and temperature for the period 2024-2050. Trend analysis of forecasted rainfall emphasizes an increasing trend for summer, monsoon, post-monsoon, and annual rainfall, whereas a negative trend is observed for winter rainfall. Trend analysis of forecasted temperature emphasizes an increasing trend for Monsoon while Annual and the rest of other seasons have negative trends.